Perancangan E-Perpustakaan Berbasis Web untuk Madrasah Ibtidaiyah Negeri 45 di Kabupaten Aceh Besar - M. Yusuf; Akbar, Rizaldi; Imilda (Jurnal Sistem Komputer (SISKOM), 2024)
This research aims to design and develop a web-based library information system tailored to the needs of Madrasah Ibtidaiyah Negeri 45 in Aceh Besar Regency, Kota Jantho District. This system aims to increase efficiency and effectiveness in managing book collections, the process of borrowing, returning and renewing books in libraries. The research methods used include literature studies to understand basic concepts in developing library information systems, observation to understand existing needs and processes in libraries, as well as system development to design and implement solutions that suit needs. The result of this research is a comprehensive web-based library information system. This system is equipped with important features such as efficient book search, library member registration, structured loan management, easy book returns, and online book loan extension. Through careful testing, this library information system is proven to work well and meet the standards of user needs. With the implementation of this system, it is hoped that there will be a significant improvement in library management, both in terms of monitoring book collections and services to users. This will make a positive contribution in improving the quality of education at Madrasah Ibtidaiyah Negeri 45 Aceh Besar Regency, Kota Jantho District.